madhavsrinivas wrote:
For which of the following does f(a)−f(b)=f(a−b) for all values of a and b?
A) f(x)=x^2
B) f(x)=x/2
C) f(x)=x+5
D) f(x)=2x−1
E) f(x)=|x|
Hi,
To solve this easiest way is just put the value and see that if it equals or not.
with option 1. f(a) = a^2 and f(b) = b^2
so L.H.S = a^2 - b^2
and R.H.S = (a-b)^2 ==> a^2 + b^2 -2ab.
so L.H.S not equal to R.H.S
with option 2. f(a) = a/2 and f(b) = b/2
L.H.S = a/2 - b/2 ==> 1/2(a-b)
R.H.S = (a-b)/2
so L.H.S = R.H.S which is the correct answer.
you can try simile for other option.
Thanks,
AB
+1 Kudos if you like and understand.